1994
DOI: 10.1093/hmg/3.4.575
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a microdeletion in 1q32–41 involving the gene responsible for Van der Woude syndrome

Abstract: Van der Woude syndrome (VWS) is an autosomal dominant craniofacial disorder representing the most frequent form of syndromic cleft lip and palate. Other characteristic features are pits of the lower lip and hypodontia. The gene shows high penetrance and seems to play an important role in orofacial development determined by the tissues involved and their formation during different periods of craniofacial development. Although most individuals affected with VWS show Mendelian inheritance, one patient with a macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
1
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 0 publications
2
44
1
1
Order By: Relevance
“…The de novo deletion spanned the entire IRF6 gene. There are at least four other documented cases which involve deletion (19)(20)(21)(22). We are designing assays to map the size of the deletion and the exact breakpoints for this chromosomal region.…”
Section: Discussionmentioning
confidence: 99%
“…The de novo deletion spanned the entire IRF6 gene. There are at least four other documented cases which involve deletion (19)(20)(21)(22). We are designing assays to map the size of the deletion and the exact breakpoints for this chromosomal region.…”
Section: Discussionmentioning
confidence: 99%
“…A 17,162-bp DNA fragment was deleted. The underlined nucleotides in the 5¢-boundary were identical to that in the 3¢-boundary families (Bocian and Walker 1987;Houdayer et al 2000;Sander et al 1994;Schutte et al 1999). Small deletions within or around the IRF6 gene, which were microscopically undetectable, also contributed to the disease, as demonstrated in this report.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal microdeletion has also been reported to cause VWS in a subset of patients (Bocian and Walker 1987;Houdayer et al 2000;Sander et al 1994;Schutte et al 1999). An analysis of microsatellite markers has revealed a 350-kb critical region of VWS (Schutte et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It was originally discovered studying a patient with typical features and a 1q32-41 deletion (Bocian & Walker, 1987). Sander et al (1994) found allele loss of a stable and highly polymorphic microsatellite (D1S205) of the 1q32-41 region in one family with Van der Woude syndrome. Schutte et al (1999) mapped a new deletion and showed that it extended 0n2-1 Mb beyond the proximal breakpoint of the deletion previously described.…”
mentioning
confidence: 99%